2021
DOI: 10.21203/rs.3.rs-141892/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Psychological Capital, Coping Style and Emotional Intelligence on Self-Rated Health Status of College Students in China During COVID-19 Pandemic

Abstract: Objective To explore the relationship between the self-reported health status, emotional coping style, emotional intelligence and positive psychological state of college students during the COVID-19 pandemic. Methods The questionnaires of Self-rated Health Measurement Scale (SRHMS), Emotional Intelligence Scale (EIS), Psychological Capital Questionnaire (PCQ), Simplified Coping Style Questionnaire (SCSQ)were used for online survey. The study included 367 undergraduates. Results Male undergraduates had signific… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Little research has also been done on protective factors (e.g., psychological capital, coping strategies, mindfulness, self-efficacy) in student samples. So far, one study showed a positive effect of psychological capital on the health status of college students during COVID-19 pandemic (Jing et al, 2021). In regard of coping strategies, Wasil et al (2021) found that behavioural activation as a coping strategy was negatively related to depression.…”
Section: Introductionmentioning
confidence: 99%
“…Little research has also been done on protective factors (e.g., psychological capital, coping strategies, mindfulness, self-efficacy) in student samples. So far, one study showed a positive effect of psychological capital on the health status of college students during COVID-19 pandemic (Jing et al, 2021). In regard of coping strategies, Wasil et al (2021) found that behavioural activation as a coping strategy was negatively related to depression.…”
Section: Introductionmentioning
confidence: 99%
“…As Cleary et al [ 19 ] explained, emotional intelligence guides the cognition drive in student academic life. Studies on emotional intelligence have received much attention over the last two decades in the Chinese context [ 20 , 21 , 22 , 23 , 24 ]. Moreover, recent studies have concentrated on the influence of emotional intelligence on behaviors and the role of training in social skills challenges in the twenty-first century [ 25 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Emotional intelligence is an important factor in helping students perceive emotions properly and in understanding the emotions of themselves and others. The emotional intelligence dimension regulates emotions through various strategies, and alleviates stressful situations through emotional intelligence knowledge [ 24 , 36 ]. In a difficult situation, a person with a good level of emotional intelligence can handle others well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…People with low emotional intelligence, on the other hand, are more prone to stress and burnout. (Jing et al, 2021). A person's good mental attitude displayed when they are growing and developing is referred to as their psychological capital.…”
Section: Introductionmentioning
confidence: 99%
“…High psychological capital scores give people the resilience and ability to deal with difficult circumstances; this lowered job burnout in the nurses with high psychological capital scores. On the other side, psychological resilience, or the capacity to "bounce back" from a poor emotional experience and confront difficult circumstances, is a key aspect in preventing nursing burnout (Jing et al, 2021 (Jing et al, 2021). These four measured and developed mental states allow people to perform more effectively.…”
Section: Introductionmentioning
confidence: 99%